A Case of Profound Bradycardia in Endurance Athlete with Severe Anorexia Nervosa - John Pueringer; Joseph Cinderella; M. Greg Treuth (Case Reports in Cardiology)
We present a case of a 54-year-old woman with asymptomatic bradycardia who was referred for consideration of a pacemaker for profound chronic sinus bradycardia (heart rate is 33 beats per minute). Further, history and physical revealed a self-described endurance athlete with severe anorexia nervosa (AN). Background. Anorexia nervosa and endurance training are known contributors to bradycardia; however, profound asymptomatic sinus bradycardia in the 20-30 beats per minute is underdocumented in the literature and not a common presentation in any setting. The decision to implant a permanent pacemaker could potentially lead to further physical and psychological repercussions in such a frail patient.